Khrushchev's putsch : reversing the socialist program and wrecking the Soviet Union - Schnehen, Gerhard, 1949- (Algora Publishing, 2020)
"In a compact book built on quotes on primary sources, Schnehen shows that Khrushchev essentially pulled off a coup, eliminating Stalin and then Beria. This opened the future to a radical shift away from the policies that had enabled the Soviet Union to make the hair-raising jump into the modern industrialized world and pulled it through the devastating war. Khrushchev reversed major achievements and brought havoc to the Soviet economy and society"--